Insurgent Planning Practices in Indonesia’s Development Planning - Zani, Nanda Mutiara; Abdi, Azizah Putri; Mukhlis, Jafar (Universitas Sulawesi Barat, 2025)
Insurgent planning represents a strand of planning theory that transcends political boundaries, challenges societal oppression, and envisions alternative urban futures. This study explores the concept and practices of insurgent planning in Indonesia through a descriptive qualitative method with a comparative approach, focusing on three major cities: Yogyakarta, Makassar, and Jakarta. The findings reveal dynamics similar to those in the Global South. In Yogyakarta, the Kalijawi Community, supported by Arkom Jogja, resisted eviction along riverbanks through social network strengthening and alternative housing initiatives. In Makassar, Kampung Pisang residents addressed tenure insecurity with Arkom Makassar via participatory mapping, negotiation, and land-sharing. In Jakarta, post-eviction residents of Kampung Akuarium reclaimed their right to the city through advocacy, litigation, and coalition-building. The study concludes that reclaiming neglected urban assets represents the most prominent form of insurgent planning, emphasising a shift from top-down approaches towards inclusive, participatory, and justice-oriented urban planning